Observation of ZZ production in pp̄ collisions at s=1.96TeV - Abazov, V. M. (2008)
We present an observation for ZZ→l+l-l′+l′- (l, l′=e or μ) production in pp̄ collisions at a center-of-mass energy of s=1.96TeV. Using 1.7fb-1 of data collected by the D0 experiment at the Fermilab Tevatron Collider, we observe three candidate events with an expected background of 0.14-0.02+0.03 events. The significance of this observation is 5.3 standard deviations. The combination of D0 results in this channel, as well as in ZZ→l+l-νν̄, yields a significance of 5.7 standard deviations and a combined cross section of σ(ZZ)=1.60±0.63(stat)-0.17+0.16(syst) pb. © 2008 The American Physical Society.